cos(a)=cos(b)⇔⎩⎨⎧aa=ou=b+2kπ−b+2kπ avec k∈Z. Ce sont les solutions sur R. sin(a)=sin(b)⇔⎩⎨⎧aa=ou=b+2kππ−b+2kπ avec k∈Z. Ce sont les solutions sur R.
cos(x)=cos(2π)⇔⎩⎨⎧xx=ou=2π+2kπ−2π+2kπ avec k∈Z. Ainsi :
S={−2π+2kπ;2π+2kπ}
avec k∈Z.
Question 2
sin(x)=sin(6π)
Correction
cos(a)=cos(b)⇔⎩⎨⎧aa=ou=b+2kπ−b+2kπ avec k∈Z. Ce sont les solutions sur R. sin(a)=sin(b)⇔⎩⎨⎧aa=ou=b+2kππ−b+2kπ avec k∈Z. Ce sont les solutions sur R.
sin(x)=sin(6π)⇔⎩⎨⎧xx=ou=6π+2kππ−6π+2kπ avec k∈Z. Finalement : ⎩⎨⎧xx=ou=6π+2kπ65π+2kπ avec k∈Z. Ainsi :
S={6π+2kπ;65π+2kπ}
avec k∈Z.
Question 3
2cos(x)−1=0
Correction
cos(a)=cos(b)⇔⎩⎨⎧aa=ou=b+2kπ−b+2kπ avec k∈Z. Ce sont les solutions sur R. sin(a)=sin(b)⇔⎩⎨⎧aa=ou=b+2kππ−b+2kπ avec k∈Z. Ce sont les solutions sur R.
2cos(x)−1=0⇔2cos(x)=1⇔cos(x)=21. Or cos(3π)=21. Cela nous ramène donc à résoudre : cos(x)=cos(3π). cos(x)=cos(3π)⇔⎩⎨⎧xx=ou=3π+2kπ−3π+2kπ avec k∈Z. Ainsi :
S={−3π+2kπ;3π+2kπ}
avec k∈Z.
Question 4
2sin(x)−2=0
Correction
cos(a)=cos(b)⇔⎩⎨⎧aa=ou=b+2kπ−b+2kπ avec k∈Z. Ce sont les solutions sur R. sin(a)=sin(b)⇔⎩⎨⎧aa=ou=b+2kππ−b+2kπ avec k∈Z. Ce sont les solutions sur R.
2sin(x)−2=0⇔2sin(x)=2⇔sin(x)=22. Or sin(4π)=22. Cela nous ramène donc à résoudre : sin(x)=sin(4π). sin(x)=sin(4π)⇔⎩⎨⎧xx=ou=4π+2kππ−4π+2kπ avec k∈Z. Finalement : sin(x)=sin(4π)⇔⎩⎨⎧xx=ou=4π+2kπ43π+2kπ avec k∈Z. Ainsi :
S={4π+2kπ;43π+2kπ}
avec k∈Z.
Question 5
−cos(x)−23=0
Correction
cos(a)=cos(b)⇔⎩⎨⎧aa=ou=b+2kπ−b+2kπ avec k∈Z. Ce sont les solutions sur R. sin(a)=sin(b)⇔⎩⎨⎧aa=ou=b+2kππ−b+2kπ avec k∈Z. Ce sont les solutions sur R.
−cos(x)−23=0⇔−cos(x)=23⇔cos(x)=−23. Or cos(65π)=2−3 Cela nous ramène donc à résoudre : cos(x)=cos(65π). cos(x)=cos(65π)⇔⎩⎨⎧xx=ou=65π+2kπ−65π+2kπ avec k∈Z. Ainsi :
S={−65π+2kπ;65π+2kπ}
avec k∈Z
Question 6
−2sin(x)−3=0
Correction
cos(a)=cos(b)⇔⎩⎨⎧aa=ou=b+2kπ−b+2kπ avec k∈Z. Ce sont les solutions sur R. sin(a)=sin(b)⇔⎩⎨⎧aa=ou=b+2kππ−b+2kπ avec k∈Z. Ce sont les solutions sur R.
−2sin(x)−3=0⇔−2sin(x)=3⇔sin(x)=−23. Or sin(−3π)=−23. Cela nous ramène donc à résoudre : sin(x)=sin(−3π). sin(x)=sin(−3π)⇔⎩⎨⎧xx=ou=−3π+2kππ−(−3π)+2kπ avec k∈Z. Finalement : sin(x)=sin(−3π)⇔⎩⎨⎧xx=ou=−3π+2kπ34π+2kπ avec k∈Z. Ainsi :